(untitled) (Bangladesh Journal of Animal Science, 2023)
The aim of this study was to investigate productive and reproductive performances, current cattle breeding practices and its associated problems in different Holstein-Local (HF×L) crossbred genotypes under existing management condition of Bangladesh. Data on HF×L crossbred dairy cows were collected from the selected farmers of Natore, Sirajganj, Kishoreganj, Tangail and Gazipur districts while breeding bulls’ information were collected from different cattle breeding service providers. Genotype had significant effects on weight at first heat (WFH), mature body weight (MBW), age at first heat (AFH), age at first calving (AFC), post-partum heat period (PPHP), daily milk yield (DMY) and peak milk yield (PMY) (P<0.05) except the traits birth weight (BW) and service per conception (SPC). The HF75%×L25% crossbreds had significantly better AFH and AFC (P<0.001) than the three genetic groups having 50%, 62.5% and >75% HF inheritance. The highest DMY was found in >HF75%×L<25% (12.80±0.72 liters) and was lowest in HF50%×L50% (5.34±0.65 liters) crossbreds. At present 11 different graded breeding bulls have been used in artificial insemination (AI) program of Bangladesh. Use of heterogeneous breeding bulls (72.9%), AI technicians depended bull’s genotype selection (63%), absence of breeding data recording (89%) system and local market-based cow purchasing (83%) with unknown pedigree information were the major challenges identified for crossbred cattle development. Among the investigated samples, 27% cows suffered from various reproductive disorders like dystocia, low conception rate, abortion and retention of placenta. In conclusion, this study provides baseline information on actual production and reproduction potentials of different graded HF×L cows at farmers’ level and the associated limiting factors for crossbred cattle development in Bangladesh. Bangladesh Journal of Animal Science 52 (3): 69-77.